EXPLORATORY STUDY OF HOW GACHA SYSTEM IN MOBILE VIDEO GAME AFFECT PLAYER’S ENJOYMENT: A CASE STUDY OF INDONESIA - Andriyanto, Andriyanto; Wibowo, Tony (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Gacha may sound familiar to our ears, even gacha in a video game is a common thing to know for players in this generation. There are certain reasons why players can feel some kind of unique excitement when playing a video game that has a gacha element. In this research, we’ve analyzed the fun factors experienced by players when playing gacha-based video games using the SEM method. Based on the results that have been obtained specifically from a total of 230 respondents, Expectation of Announcement strongly influences Gacha and Satisfaction of Announcement slightly influences Gacha. Therefore, players can feel enjoyed and more excited because of how the gacha system is implemented in a video game that is played. In addition, even when rolling the gacha itself is one of the things that can be enjoyed by players.